Mongolia and 14th Dalai Lama in Late 20th and 21st Centuries - V. A. Rodionov; O. Khatanbold (Научный диалог, 2024)
This study explores the role of the Dalai Lama institution in the political processes of Mongolia, both from a historical perspective and in the context of contemporary events. The aim of the article is to identify the key factors influencing the presence of the Dalai Lama in Mongolia’s socio-political life. Conceptually and methodologically, the research relies on the theory of post-secular society. The sources for this study include legal documents from Mongolia, data from national censuses, results from sociological surveys, and publications from Mongolian, Russian, and Western media that address the relationships between state, society, and religion. The authors argue that modern Mongolia exemplifies a post-secular society. It is noted that the abandonment of state atheism and the phenomenon of “Buddhist revival” have led to a significant intertwining of religious and secular institutions. The figure of the 14th Dalai Lama is regarded as a crucial participant in these processes. The study establishes that the main factors contributing to the involvement of the Dalai Lama in Mongolia’s socio-political processes include his high religious authority among believers, the legitimization of Mongolian reincarnations, and his image as a “democratic leader.” Factors that restrain the influence of the Dalai Lama include a significant segment of non-religious citizens in Mongolia, risks of deteriorating relations with the People’s Republic of China, and trends toward the nationalization of Mongolia’s Buddhist sangha.